Analysis Of the Ministry of ATR/BPN Employee Scholarship Program in The Framework of The Realization of The Concept of Walfare State of The United State of The Republic of Indonesia - Setiawan, Agung; Umam, Khairul; Amalia, Riska Ari; Rahmadani, Rahmadani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The Welfare State ideology teaches about the role of the State which is broader than the